Communication Strategy of PT Timah Tbk in Managing Crisis - Anggi Budiman Siahaan; Fitria Febriyola; Muhammad Ismunadi (Asian Journal of Social and Humanities, 2025)
This study discusses how a company in the mining sector that is vulnerable to social conflict is required to design and implement an effective and targeted corporate communication strategy with the aim of reducing interference with reputation. In this case, Corporate Communication PT TIMAH Tbk as the object of research, faced a potentially crisis event with a fire on its production equipment, namely Kapal Druk Singkep 1. This study is a qualitative research with the results in the form of descriptive data. Data collection techniques were obtained through in-depth interviews with several internal informants, namely: External Relations Manager of PT Timah Tbk, Social Media and Website Manager of PT Timah Tbk, Compliance Division of PT Timah Tbk and external informants of the company, namely Tribunbangka.com. the validity of the data in this study using data triangulation. Data analysis in qualitative research is done by data reduction, data presentation, and draw conclusions. This study found the facts related to the communication strategy carried out by PT TIMAH Tbk which was carried out with the communication planning stages, which included: research, planning, implementation, evaluation and reporting, where it was later found that the application of the stages of communication work was considered successful with the indicators found in the evaluation stage.